Application of water-soluble conjugated polymers in intelligent measurement and control of food microbial fermentation process - Liu, Chang; Tang, Yujiao (Frontiers in Chemistry, 2023)
Due to insufficient measurement and control (MAC) methods and complex operations, the fermentation process of food microorganisms is not convenient, and it is difficult to achieve MAC of the fermentation process in extreme brewing environments. In order to change the difficulty of measuring and controlling the fermentation process, this paper applied water-soluble conjugated polymer to the sensor, carried out data modeling and prediction, and integrated the sensor into the intelligent MAC system. This article selected fermentation rate, product yield, and energy consumption efficiency as evaluation indicators to analyze the effectiveness of intelligent MAC. The MAC method based on water-soluble conjugated polymers in this article was compared and analyzed with traditional MAC methods. In laboratory experimental analysis, it was found that the MAC method based on water-soluble conjugated polymers can improve product yield, fermentation efficiency, and energy utilization compared to traditional MAC methods. In the data analysis experiment, it was found that the MAC accuracy, timeliness, stability, speed, and safety of the MAC system based on water-soluble conjugated polymers were higher than those of traditional MAC systems. Among them, the average test stability of traditional MAC systems was 19.93% lower than that of intelligent MAC systems based on water-soluble conjugated polymers. In practical application verification, it was found that the application of intelligent MAC methods based on water-soluble conjugated polymers can improve the yield of wine and is feasible.